Predicament and Response: an Introduction - Beckman, Bjorn; Adeoti, Gbemisola (2014)
Progressives in Africa keep debating and agonizing over the failure of the forces on the ground to advance the material, social and political welfare of the continent, the African predicament. This article discusses the response of some of Africa's leading intellectuals-cum-writers: Soyinka, Ngugi, Achebe.